2018
DOI: 10.1002/ejoc.201800860
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen‐Bonding Interactions in the Ley–Griffith Oxidation: Practical Considerations for the Synthetic Chemist

Abstract: The Ley–Griffith oxidation, which is catalyzed by tetra‐n‐propylammonium perruthenate (TPAP, nPr4N[RuO4]), is a popular method for not only controlled oxidation of primary alcohols to aldehydes, but also a host of other synthetically useful transformations. While the fundamental reaction mechanism has recently been elucidated, several key hydrogen‐bonding interactions between the reagents were implicated but not investigated. Herein the prevalence of H‐bonding between the co‐oxidant N‐methylmorpholine N‐oxide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…It is well-known that transition metal complexes play a crucial role in oxidation process. Many transition metal catalysts including ruthenium (Shapley et al, 2000; Lybaert et al, 2017; Sarbajna et al, 2017; Moore et al, 2019), palladium (Stahl, 2004; Sigman and Jensen, 2006; Ho et al, 2018), copper (Velusamy et al, 2006; Jehdaramarn et al, 2018; Lagerspets et al, 2019), and iron (Coleman et al, 2010; Stanje et al, 2018) have been reported for promoting the oxidation of alcohols. Among them, ruthenium compounds are intensively studied because of their rich structures and various valence states.…”
Section: Introductionmentioning
confidence: 99%
“…It is well-known that transition metal complexes play a crucial role in oxidation process. Many transition metal catalysts including ruthenium (Shapley et al, 2000; Lybaert et al, 2017; Sarbajna et al, 2017; Moore et al, 2019), palladium (Stahl, 2004; Sigman and Jensen, 2006; Ho et al, 2018), copper (Velusamy et al, 2006; Jehdaramarn et al, 2018; Lagerspets et al, 2019), and iron (Coleman et al, 2010; Stanje et al, 2018) have been reported for promoting the oxidation of alcohols. Among them, ruthenium compounds are intensively studied because of their rich structures and various valence states.…”
Section: Introductionmentioning
confidence: 99%
“…[5] In contrast to this, high reaction states were postulated in the literature to drive the Griffith-Lay oxidation. [2,6] In course of a study on the oxidation of alcohols from natural resources, we were looking for catalyst systems giving optimum yields and selectivities in the dehydrogenation of alcohols to aldehydes and ketones in the presence of a reasonably priced oxidizing agent. We therefore revived the protocol of Sharpless and co-workers under these basic conditions.…”
Section: Introductionmentioning
confidence: 99%